Ketahanan Ekonomi Pada Masa Pandemi Covid-19 Ditinjau dari Aspek Modal Sosial dan Motivasi Masyarakat Manggarai Barat, Labuan Bajo, Nusa Tenggara Timur - Hadiningrat, Mohamad Axel Putra; Rusliwa Somantri , Gumilar; Hasan, Chotib; Nurbaiti, Beti (Jurnal Keamanan Nasional, 2023)
This study aims to analyze the determinants of social capital and motivation for the economic resilience of the West Manggarai community in Labuan Bajo, East Nusa Tenggara during the COVID-19 pandemic. The research used a deductive/quantitative approach which was conducted from 24 July to 2 August 2022. This research was limited to only 300 respondents in West Manggarai, Labuan Bajo, and East Nusa Tenggara with a questionnaire instrument. The results of quantitative data processing are enriched by in-depth interviews. The data is further processed to produce descriptive statistical analysis and the results of processing the influence of latent variables using the Structural Equation Modeling (SEM) concept with Lisrel software. The results of the study concluded that there was a significant influence / positive correlation between social capital and the economic resilience motivation of the people of West Manggarai, Labuan Bajo, and East Nusa Tenggara. Social capital is an intangible asset that has not been used optimally in the community empowerment process by local policymakers. Positive social capital will have a positive impact on people’s motivation to live better in fulfilling their daily needs, to achieving good economic resilience.